STEVENS INSTITUTE OF TECHNOLOGY: WEBCAMPUS - Ubell, Robert N. (Online Learning, 2004)
WebCampus.Stevens, recent winner of the Sloan-C Award for Excellence in Institute-Wide Online Teaching and Learning Programming, delivers some 160 courses in six online graduate degrees and 23 graduate certificates. Taught by more than 60 mostly full-time faculty, courses have now enrolled more than 4,000 students in 37 US states and in 28 countries abroad since it was launched in 2000. Paralleling those on campus, online courses are taught by the same faculty who teach face-to-face, using the same content. Online and on campus, students meet the same high standard, pay the same tuition, and receive the same degrees. Resolution of online intellectual property rights by Stevens has become a model for other online schools with faculty retaining rights for all other uses but online. Arrangements have been made with prominent engineering societies and industry associations to offer courses to nearly 800,000 members worldwide.WebCampus delivers Chinese graduate students at Beijing Institute of Technology a hybrid Master's program. The school is developing remote laboratories for online learners.